Ottoman Rule of Law and the Modern Political Trial : The Yildiz Case - Rubin, Avi, 1971- (Book collections on Project MUSE., 2018)
"'Ottoman Rule of Law and the Modern Political Trial' employs a socio-legal approach to analyze the famous yet understudied 'Yildiz Trial, ' surrounding the 1876 death of Sultan Abdülaziz, and this trial's representations in contemporary public discourses and subsequent historiography"--